2002
DOI: 10.1046/j.0960-7412.2001.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Selenate‐resistant mutants of Arabidopsis thaliana identify Sultr1;2, a sulfate transporter required for efficient transport of sulfate into roots

Abstract: SummaryTo investigate how plants acquire and assimilate sulfur from their environment, we isolated and characterized two mutants of Arabidopsis thaliana de®cient in sulfate transport. The mutants are resistant to selenate, a toxic analogue of sulfate. They are allelic to each other and to the previously isolated sel1 (selenate-resistant) mutants, and have been designated sel1-8 and sel1-9. Root elongation in these mutants is less sensitive to selenate than in wild-type plants. Sulfate uptake into the roots is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
315
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 367 publications
(329 citation statements)
references
References 30 publications
10
315
1
3
Order By: Relevance
“…We showed that the expression of endogenous S-responsive genes was also up-regulated in osh1-1. During the course of this study, a mutant having a lesion in the sulfate transporter 1;2 gene (Shibagaki et al, 2002;Yoshimoto et al, 2002) was also isolated (N. Ohkama-Ohtsu, Y. Ide, and T. Fujiwara, unpublished data), which supports the validity of our screening strategy. To our (Arunachalam et al, 2000) are italicized and underlined, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…We showed that the expression of endogenous S-responsive genes was also up-regulated in osh1-1. During the course of this study, a mutant having a lesion in the sulfate transporter 1;2 gene (Shibagaki et al, 2002;Yoshimoto et al, 2002) was also isolated (N. Ohkama-Ohtsu, Y. Ide, and T. Fujiwara, unpublished data), which supports the validity of our screening strategy. To our (Arunachalam et al, 2000) are italicized and underlined, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…We have recently characterized the function of two distinct high-affinity sulfate transporters, Sultr1;1 and Sultr1;2, that facilitate the initial uptake of sulfate at the root epidermis and cortex in Arabidopsis (Shibagaki et al, 2002;Yoshimoto et al, 2002). In the present study, a putative open reading frame, At1g22150, that potentially encodes the third isoform of the high-affinity sulfate transporter in Arabidopsis was identified on the BAC clone F2E2 (accession no.…”
Section: Identification Of a Novel High-affinity Sulfate Transportermentioning
confidence: 99%
“…In the past few years, numbers of genes encoding high-affinity sulfate transporters in vascular plants have been isolated and characterized (Smith et al, 1995(Smith et al, , 1997Vidmar et al, 1999;Takahashi et al, 2000;Shibagaki et al, 2002;Yoshimoto et al, 2002). These high-affinity sulfate transporters are predominantly expressed in roots of sulfur-starved plants and are suggested to serve for the initial uptake of sulfate from the soil.…”
mentioning
confidence: 99%
See 2 more Smart Citations